Berberine combined with stachyose induces better glycometabolism than berberine alone through modulating gut microbiota and fecal metabolomics in diabetic mice. (13th December 2019) - Li, Cai‐Na; Wang, Xing; Lei, Lei; Liu, Min‐Zhi; Li, Rong‐Cui; Sun, Su‐Juan; Liu, Shuai‐Nan; Huan, Yi; Zhou, Tian; Liu, Quan; Cao, Hui; Bai, Guo‐Liang; et al.
Abstract : Berberine (BBR), a small alkaloid, is used as a hypoglycemic agent in China. Stachyose (Sta), a Rehmannia glutinosa oligosaccharide, acts as a prebiotic. This study aimed to evaluate whether BBR combined with Sta produced better glycometabolism than BBR alone, and explored the effects on gut microbiota and metabolomics. Type‐2 diabetic db/db mice were administered BBR (100 mg/kg), Sta (200 mg/kg), or both by gavage once daily. Glucose metabolism, the balance of α‐ and β‐cells, and mucin‐2 expression were ameliorated by combined treatment of BBR and Sta, with stronger effects than upon treatment with BBR alone. The microbial diversity and richness were altered after combined treatment and after treatment with BBR alone. The abundance of Akkermansia muciniphila was increased by combined treatment compared to treatment with BBR alone, while the levels of the metabolite all‐trans‐heptaprenyl diphosphate were decreased and the levels of fumaric acid were increased, which both showed a strong correlation with A. muciniphila . In summary, BBR combined with Sta produced better glycometabolism than BBR alone through modulating gut microbiota and fecal metabolomics, and may aid in the development of a novel pharmaceutical strategy for treating Type 2 diabetes mellitus.